Hydrodynamic Analysis of Pipelines Transporting Capsule for Onshore Applications (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract— Rapid depletion of energy resources hasimmensely affected the cargo transportation industry.Efforts have been made to develop newer economic andenvironmental friendly modes for this purpose. Bulk solidscan be transported for long distances effectively in pipelines.Raw materials can be stored in spherical containers(commonly known as capsules) transported through thepipeline. For economical and efficient design of anytransportation mode, both the local flow characteristics andthe global performance parameters need to be investigated.Published literature is severely limited in establishing theeffects of local flow features on system characteristics ofHydraulic Capsule Pipelines (HCPs). The present study focuses on using a well-validatedComputational Fluid Dynamics (CFD) based solver tosimulate the unsteady turbulent flow of a sphericalcapsule as a simplified case in HCPs for onshoreapplications. A novel numerical model has beenemployed in the present study with the aid of thedynamic mesh technique for calculating the pressureand the velocity variations within such pipelines. Thenumerical model comprises a straight test section. Thenumerical model for capsule flow yields realisticresults for the global flow parameters as compared tothe experimental data from the test rig developed inthe present study. The influence of the carrying fluid(water) on the capsule has been verified by estimatingthe shear forces and the friction coefficient. Inaddition, novel models have been developed forpredicting the wet friction coefficient considering thestart-up effect in such systems.